PENGARUH PEMBERIAN SAYUR REBUSAN DAUN KATUK TERHADAP PRODUKSI ASI PADA IBU MENYUSUI DI WILAYAH KERJA PUSKESMAS TRUMON KABUPATEN ACEH SELATAN - Hafsah Us; Mey Elisa Safitri (Jurnal Ilmiah Kebidanan Imelda, 2025)
Babies are the most beautiful gift given by the creator to man. Exclusive breastfeeding can also help the baby for growth and development later. Physically he gets enough nutrition, far more than everything the world has to offer. The aim of this study is to explore the effects of consuming Katuk leaf stew on breastfeeding mothers' breast milk production in the Trumon Health Center Area, South Aceh district. The research design applied is qualitative, incorporating pseudo-experimental methods. In this study, all 15 participants were mothers who breastfeed, with a total of 15 individuals included in the sample selected through Total Sampling. Various methods are involved in collecting data, including primary, secondary, and tertiary sources. The data analysis involves employing both univariate and bivariate analysis techniques, alongside utilizing the chi-square test. The research findings showed that most participants, around 80. 0%, were between the ages of 20 and 30. Additionally, all 15 individuals (100%) receiving katuk leaf stew reported an enhanced breast milk production. Giving a decoction of katuk leaf vegetables to nursing mothers affects milk production.  Conclusion of this research giving a decoction of katuk leaf vegetables to nursing mothers affects milk production. It is expected that breastfeeding mothers are able to further improve the health of mothers and babies, especially breastfeeding mothers know more about the benefits of katuk leaves so as to support the success of exclusive breastfeeding.